Penanaman Pendidikan Karakter Melalui Pembelajaran Tematik Kelas IV - Citra Noharlin Salsabila; Suyanti Suyanti; Heny Kusuma Widyaningrum (Prosiding Konferensi Ilmiah Dasar, 2022)
This study aims to describe the process of implementing character education through thematic learning, describing character values and obstacles in implementing character education planting in thematic learning in grade IV. This study uses a qualitative approach with a descriptive type. The subjects of this research are fourth grade teachers, principals, students. This research was conducted at SDN Patalan 1. The data collection techniques used were observation, interviews, and documentation. The data analysis technique is carried out with the stages of data reduction, data presentation and presentation of conclusions. The results of this study indicate that: 1) Planning for the implementation of character education in thematic learning begins with compiling various learning tools such as lesson plans, syllabus, semester programs. (2) In terms of implementation, the teacher implements it through classroom learning activities through the preliminary, core and closing stages by integrating the teacher's character values through classroom learning by applying examples in everyday life. (3) The obstacles faced by teachers in implementing character education are limited infrastructure facilities.